Pengaruh Operating Profit Margin (OPM), Return On Equity (ROE), Dan Return On Assets (ROA) Terhadap Harga Saham Pada PT. Xl Axiata Tbk Tahun 2019-2023 - Fitriyani, Dwi; Hartono; Dwihandoko, Toto Heru (PT. Kreasi Karya Majakata, 2024)
In general, companies listed on the stock market prioritize share price increases as a measure of their value. This was done in an effort to attract investors to contribute to the business. Various variables that influence stock prices include profitability, Operating Profit Margin (OPM), Return On Assets (ROA), and Return On Equity (ROE). In theory, profits in Operating Profit Margin (OPM), Return On Equity (ROE), and Return On Assets (ROA) are correlated with higher stock prices, however, at PT. XL Axiata Tbk., these three ratios experienced fluctuations from 2019 to 2023, even in 2023 they indicated an increase. PT. XL Axiata Tbk, but share prices are expected to fall in 2022–2023. The aim of this research is to examine the influence of Operating Profit Margin (OPM), Return On Equity (ROE), and Return On Assets (ROA) on stock prices. In this research, multiple linear regression analysis was used to analyze quantitative data using the SPSS (Statistics Product and Service Solution) application program. Based on the research results, there is no real relationship between stock prices and Operating Profit Margin (OPM), Return on Equity (ROE), and Return on Assets (ROA), with respective significance values ??of 0.467, 0.134, and 0.157.